Legal Frameworks for Smart City Governance: Balancing Technological Innovation and Citizen Privacy in Jakarta - Hafiz Sutrisno; Clara Mendes; Raul Gomez (Rechtsnormen: Journal of Law, 2025)
Background. The rapid deployment of smart city technologies in Jakarta has transformed urban governance, enabling data-driven decision-making and enhanced public services. However, this transformation also raises complex legal and ethical challenges related to data protection, surveillance, and citizens’ digital rights. Purpose. This study aims to analyze the existing legal frameworks that regulate smart city governance in Jakarta and evaluate their effectiveness in balancing technological innovation with the protection of citizen privacy.   Method. A qualitative legal research method was employed, combining normative juridical analysis with policy review and expert interviews to examine statutory instruments, regulatory gaps, and institutional practices. Results. The results reveal that while Indonesia’s data protection legislation provides a foundational basis for digital governance, inconsistencies in implementation and weak interagency coordination hinder comprehensive enforcement. The governance framework remains technologically progressive yet legally fragmented, lacking clear accountability mechanisms for data handling and public transparency. Conclusion. The study concludes that Jakarta’s smart city model requires a more integrated and adaptive legal architecture that aligns innovation objectives with citizen-centric principles. Strengthening regulatory harmonization and participatory governance is crucial to ensuring sustainable, ethical, and rights-based smart city development.